Understanding Short-Term and Long-Term Price Fluctuations of Main Staple Food Commodities in Aceh Province, Indonesia: An ARDL Investigation - Putra, Hadi Arisyah; Fijay, Ade Habya; Suriani, Suriani; Seftarita, Chenny; Ringga, Edi Saputra; Wintara, Heri; Fadliansah, Oka (Ekonomikalia Journal of Economics, 2023)
Aceh Province still relies on external sources from other regions for its main staple food commodities, resulting in unpredictable price fluctuations. To address this issue, it is essential to identify the key determinants responsible for these fluctuations and implement suitable preventive measures and policies. Utilizing monthly time-series data from January 2016 to December 2020 and employing the Autoregressive Distributed Lag (ARDL) approach, we investigate the short-term and long-term impact of variables like raw material prices, rainfall, and price index received by farmers on the price fluctuations. The results of the ARDL estimation reveal that all selected independent variables play a crucial role and significant in influencing the price fluctuations of main staple food commodities. Armed with these findings, we suggest that policymakers can provide necessary resources to farmers, strengthen weather monitoring systems, and enhance market transparency, thus better controlling future price fluctuations of regional staple food commodities.